Brain activation during cognitive planning in twins discordant or concordant for obsessive–compulsive symptoms - den Braber, Anouk (Oxford University Press, 2010)
Neuroimaging studies have indicated abnormalities in cortico-striatal-thalamo-cortical circuits in patients with obsessive–compulsive disorder compared with controls. However, there are inconsistencies between studies regarding the exact set of brain structures involved and the direction of anatomical and functional changes. These inconsistencies may reflect the differential impact of environmental and genetic risk factors for obsessive–compulsive disorder on different parts of the brain. To distinguish between functional brain changes underlying environmentally and genetically mediated obsessive–compulsive disorder, we compared task performance and brain activation during a Tower of London planning paradigm in monozygotic twins discordant (n = 38) or concordant (n = 100) for obsessive–compulsive symptoms. Twins who score high on obsessive–compulsive symptoms can be considered at high risk for obsessive–compulsive disorder. We found that subjects at high risk for obsessive–compulsive disorder did not differ from the low-risk subjects behaviourally, but we obtained evidence that the high-risk subjects differed from the low-risk subjects in the patterns of brain activation accompanying task execution. These regions can be separated into those that were affected by mainly environmental risk (dorsolateral prefrontal cortex and lingual cortex), genetic risk (frontopolar cortex, inferior frontal cortex, globus pallidus and caudate nucleus) and regions affected by both environmental and genetic risk factors (cingulate cortex, premotor cortex and parts of the parietal cortex). Our results suggest that neurobiological changes related to obsessive–compulsive symptoms induced by environmental factors involve primarily the dorsolateral prefrontal cortex, whereas neurobiological changes induced by genetic factors involve orbitofrontal–basal ganglia structures. Regions showing similar changes in high-risk twins from discordant and concordant pairs may be part of compensatory networks that keep planning performance intact, in spite of cortico-striatal-thalamo-cortical deficits.